Advancing universal health coverage in South Asian cities: A framework - Adams, Alayne M; Nambiar, Devaki; Siddiqi, Sameen; Alam, Bushra Binte; Reddy, Srinath (BMJ Open, 2022)
This article was published in the BMJ [Copyright © 2018, BMJ Publishing Group Ltd ] and the definite version is available at: https://doi.org/10.1136/bmj.k4905 The Journal's website is at: https://www.bmj.com/content/363/bmj.k4905.full